Effects of Multimedia Learning Program on Knowledge and Practices for Respiratory Infection Prevention Among Prison Health Volunteers: A Pilot Study - Plubplatong, Puttaya; Sripetchwandee, Noppamas; Aungwattana, Sivaporn (Journal of The Royal Thai Army Nurses, 2026)
Respiratory infectious diseases are a major public health concern due to their rapid transmission, particularly in overcrowded settings such as prisons, where hygiene is inadequate. Prison Health Volunteers (PHVs) play a vital role as health leaders in preventing such diseases. This quasi-experimental research using a one-group pretest–posttest design aimed to compare the knowledge and practices of PHVs regarding the prevention of respiratory infectious diseases, before and after participation in a multimedia learning program. The participants consisted of 20 PHVs. The research instruments included a multimedia learning activity plan, a printed knowledge manual, and instructional video clips on knowledge and preventive practices for respiratory infections in prisons. The program was implemented over four weeks, with an evaluation conducted in the sixth week. The results showed that the median scores for knowledge and preventive practices after participation (Median= 11.48, IQR = 1.15) (Median = 40.15, IQR = 2.54) were significantly higher than those before the program (Median = 8.85, IQR = 1.69) (Median = 29.30, IQR = 2.47) (p < .001). These findings indicate that the multimedia learning program effectively enhanced both knowledge and practices in preventing respiratory infectious diseases among PHVs. and can be further applied to strengthen disease prevention and control efforts in correctional facilities.